Relasi Manajemen Masjid dan Kegiatan Keagamaan Islam: Studi di Masjid Dawamul Ijtihad Semarang - Wahyu Khoiruz Zaman (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
This study aims to find out how mosque management improves Islamic religious activities and what are the supporting and inhibiting factors in increasing Islamic religious activities. Islamic religious activities at the Dawamul Ijtihad Mosque in Semarang. This research uses a qualitative method and a descriptive approach. Data collection techniques were carried out by (1) observation, (2) interviews, and (3) documentation. Analysis of data collection using (1) data reduction, (2) data presentation, (3) comparative analysis, and (4) drawing conclusions. Testing the validity of the data was carried out by (1) extending the observations, (2) increasing persistence, (3) using reference materials. Researchers obtained interview data with mosque administrators and members of the Dawamul Ijtihad Semarang Mosque. The results of this study indicate that the mosque management implemented at the Dawamul Ijtihad Mosque in Semarang is in accordance with the management functions carried out in managing Islamic religious activities at the mosque. Includes planning, organizing, implementing, and supervising. In implementing mosque management there are several supporting factors, namely, good communication is established between administrators and the surrounding community. Secondly, mosque administrators have selected imams and teachers as well as reliable recitation speakers in order to increase Islamic religious activities. Third, the mosque has complete infrastructure and strategic layout of the mosque. But on the other hand there are also several inhibiting factors, namely, the lack of human resources and the younger generation who are interested in managing the mosque. Second, public awareness in the prosperity of mosques or participating in Islamic religious activities still needs to be increased